MENJELASKAN METODE PEMBELAJARAN SEUSIA REMAJA - Anakoda, Wadira; Risalatul Aulia, Agits; Puspitasari, Selvi; Munasir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article discusses the importance of selecting and applying learning models that are relevant to the psychological characteristics and social context of adolescents in the postmodern and digital era. As the internet generation, adolescents require learning approaches that integrate mastery of academic content with character development and critical thinking. Through a conceptual study of the functions, objectives, and principles of national education as mandated by Law Number 20 of 2003, this article emphasizes that the goal of education is to develop Indonesian individuals who are faithful, morally upright, creative, independent, and possess Pancasila-based character. Three learning models—exemplary learning, brain-based learning, and e-learning—are examined within this framework and considered relevant for adolescents. The exemplary learning model positions educators as role models in all aspects of life, not only in the classroom. Brain-based learning emphasizes experiential learning and the optimization of brain function through contextual and meaningful activities. Meanwhile, e-learning offers flexibility and the use of digital technology that aligns with the characteristics of today’s adolescent generation. This study concludes that no single learning model is entirely ideal; therefore, an innovative and collaborative approach that integrates multiple models is necessary to address contemporary challenges and achieve national education goals.